Farmers’ experience with subsidy scheme on power tillers to enhance farm mechanization in India - SINGH, A K; PAUL, KESHAVA S; BURMAN, R ROY; PAUL, SUDIPTA; SOM, SUKANYA; KUMAR, ANJANI; DEKA, B C; TRIPATHI, A K; PRASAD, Y G (The Indian Journal of Agricultural Sciences, 2020)
Realizing the importance of farm mechanization in purview of shortage of farm labour and increasing demand from land for higher productivity, the Government of India implemented a subsidy scheme for promoting purchase and use of power tillers by farmers during 2007–2015. The present study aimed at assessing perception of the beneficiaries about the status of implementation of the scheme with a focus on power tiller purchase, use, and hindrances (if any). The study was conducted in randomly selected 23 districts from 5 purposively selected states of India with a total of 746 beneficiary farmers (n=746). Primary cross sectional data were collected with the help of a structured personal interview schedule. Variation was noticed among the states regarding cost and subsidy received to buy the power tillers. The average cost of power tillers including subsidy, was the highest for Tripura (`₹ 171577) followed by Assam (`₹ 169317). The average amount of subsidy was ` ₹ 70701 with the highest reported in Andhra Pradesh (` ₹ 90626). Overall, a majority (91.96%) of the respondents reported not to face difficulties in availing the subsidy. Overall 89.01% of the beneficiaries expressed satisfaction with the quality of power tillers supplied under the scheme. However, more than half of the beneficiaries were not satisfied with the overall services provided by the dealers including training and maintenance services. The findings of the study will be helpful for policy makers to evaluate the scheme and make improvements based on the lacuna investigated in the study.